2015
DOI: 10.3102/0034654315577210
|View full text |Cite
|
Sign up to set email alerts
|

Gameplay Engagement and Learning in Game-Based Learning

Abstract: In this review, we investigated game design features that promote engagement and learning in game-based learning (GBL) settings. The aim was to address the lack of empirical evidence on the impact of game design on learning outcomes, identify how the design of game-based activities may affect learning and engagement, and develop a set of general recommendations for GBL instructional design. The findings illustrate the impact of key gaming features in GBL at both cognitive and emotional levels. We also identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
133
0
10

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 367 publications
(191 citation statements)
references
References 105 publications
8
133
0
10
Order By: Relevance
“…There is a growing body of literature supporting the use of serious games to enhance learning and engagement in education, from kindergarten through to postsecondary levels (for recent meta-analyses and reviews, see Abdul Jabbar & Felicia, 2015;Clark et al, 2016;Boyle et al, 2016;Wouters et al, 2013). However, most studies investigate whether or not the serious game facilitates learning, rather than focusing on how the game design facilitates learning (Clark et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…There is a growing body of literature supporting the use of serious games to enhance learning and engagement in education, from kindergarten through to postsecondary levels (for recent meta-analyses and reviews, see Abdul Jabbar & Felicia, 2015;Clark et al, 2016;Boyle et al, 2016;Wouters et al, 2013). However, most studies investigate whether or not the serious game facilitates learning, rather than focusing on how the game design facilitates learning (Clark et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Many empirical studies carried out in the last decade have explored the impact of entertainment and/or serious games on motivation and learning (Abdul Jabbar & Felicia, 2015;Ke, 2016;Koutromanos, Sofos, & Avraamidou, 2015;Young et al, 2012); others investigated how game mechanics can be tailored for specific educational goals (Lameras et al, 2017). The overarching objective of these research efforts has been to seek evidence of games' educational effectiveness and to optimize game-based learning design.…”
Section: State Of the Artmentioning
confidence: 99%
“…Roemmich, Lambiase, McCarthy, Feda and Kozlowski (2012) added to this definition that AVGs intrinsically encourage support shared (2014) also concluded that AVGs are a solution which inspires and motivates people to exercise. Finally, Abdul and Felicia (2015) explained that participants' use of AVGs exerted great influence on both cognitive and emotional levels. These attributes might explain why several youths choose AVG play over traditional exercise (Papastergiou, 2009).…”
Section: Introductionmentioning
confidence: 99%